The characterization of tourmaline and its effects on plant growth - Huang, Sin-Yi; Yu, Chun Ming; Liu, Po-Yuan; Yu, Yun-Hseng; Chen, Chien Hung; Liu, Ching Fung; Juang, Yaju (Centre for Science and Technology, IAIN Surakarta, 2017)
The purpose of this study was to investigate the characteristics of ACERALIVEN™, a commercial tourmaline, and to test its effect on plant growth. According to our analysis, ACERALIVEN™ belongs to the Si-Al-Mg tourmaline structure. It contains some trace metals such as zirconium, potassium, and iron and able to emit far-infrared energy in the emissivity of 0.829. Introducing the tourmaline into water changes the water to be more alkaline. Tourmaline also releases negative hydroxyl ions and dissolved oxygen creating what is called as hydrogen water. Mung beans submerged with ACERALIVEN™ shows a longer lifetime than without submerging the tourmaline.  Additionally, the tourmaline can promote plant growth by removing chlorine and releasing far-infrared which is beneficial for plant’s metabolism.